If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5-5x=2(4+3x)
We move all terms to the left:
-5-5x-(2(4+3x))=0
We add all the numbers together, and all the variables
-5x-(2(3x+4))-5=0
We calculate terms in parentheses: -(2(3x+4)), so:We get rid of parentheses
2(3x+4)
We multiply parentheses
6x+8
Back to the equation:
-(6x+8)
-5x-6x-8-5=0
We add all the numbers together, and all the variables
-11x-13=0
We move all terms containing x to the left, all other terms to the right
-11x=13
x=13/-11
x=-1+2/11
| x/14-10=-11 | | 17=x/3-13 | | 3/(x+8)=2/(x+14) | | -30x-50=120 | | 13v-12v=16 | | 5(x+4)=2x+44 | | (2m-10)=2.3m+10 | | 5(1-13b)+2b=383 | | -4+x/6=-5 | | 2398=14(2-13x)+4 | | -2+v=-9 | | -13(11-14x)=-2509 | | -287=7(6x-5) | | 10-3x=4x-5 | | -10(2p-14)-7p=329 | | 4(x+1)+4x-5=9 | | 4y+3y=7y | | -1170=6(1=14n) | | 7x-(2x+5)=x+47 | | 3v+2=45 | | 7x-2x+5)=x+47 | | 13(-8b-14)=14b=-182 | | -3(x-1)+8(×-3)=6x+7-5x | | -12k-–14k+-13k=-11 | | -160=-10b | | -17g=-3g | | 3=k6 | | 1200=x-35x/100 | | -3(x-1+8(×-3)=6x+7-5x | | -2(x-4)+3=-×-1 | | 4p-p=12 | | 18b-17b=15 |